Reduced renal sympathetic nerve activity contributes to elevated glycosuria and improved glucose tolerance in hypothalamus-specific Pomc knockout mice - Kavaljit H. Chhabra; Donald A. Morgan; Benjamin P. Tooke; Jessica M. Adams; Kamal Rahmouni; Malcolm J. Low (Elsevier, 2017)
Objective: Hypothalamic arcuate nucleus-specific pro-opiomelanocortin deficient (ArcPomc−/−) mice exhibit improved glucose tolerance despite massive obesity and insulin resistance. We demonstrated previously that their improved glucose tolerance is due to elevated glycosuria. However, the underlying mechanisms that link glucose reabsorption in the kidney with ArcPomc remain unclear. Given the function of the hypothalamic melanocortin system in controlling sympathetic outflow, we hypothesized that reduced renal sympathetic nerve activity (RSNA) in ArcPomc−/− mice could explain their elevated glycosuria and consequent enhanced glucose tolerance. Methods: We measured RSNA by multifiber recording directly from the nerves innervating the kidneys in ArcPomc−/− mice. To further validate the function of RSNA in glucose reabsorption, we denervated the kidneys of WT and diabetic db/db mice before measuring their glucose tolerance and urine glucose levels. Moreover, we performed western blot and immunohistochemistry to determine kidney GLUT2 and SGLT2 levels in either ArcPomc−/− mice or the renal-denervated mice. Results: Consistent with our hypothesis, we found that basal RSNA was decreased in ArcPomc−/− mice relative to their wild type (WT) littermates. Remarkably, both WT and db/db mice exhibited elevated glycosuria and improved glucose tolerance after renal denervation. The elevated glycosuria in obese ArcPomc−/−, WT and db/db mice was due to reduced renal GLUT2 levels in the proximal tubules. Overall, we show that renal-denervated WT and diabetic mice recapitulate the phenotype of improved glucose tolerance and elevated glycosuria associated with reduced renal GLUT2 levels observed in obese ArcPomc−/− mice. Conclusion: Hence, we conclude that ArcPomc is essential in maintaining basal RSNA and that elevated glycosuria is a possible mechanism to explain improved glucose tolerance after renal denervation in drug resistant hypertensive patients.